Dust emissions from Kati Thanda-Lake Eyre: a review. Issue 1 (2nd January 2022) - Marx, S.K.; May, J-H; Cohen, T.; Kamber, B.S.; McGowan, H.A.; Petherick, L.
ABSTRACT: Kati Thanda-Lake Eyre (KT-LE) sits at the heart of Australia's dust transport system. Satellite mapping demonstrates that the lower Channel Country/northern KT-LE represents a global dust hotspot – the largest in the Southern Hemisphere. This dust is transported widely, with two dominant plume pathways; southeast, across the Tasman Sea, South Pacific Ocean and Southern Ocean, and northwest over the Pilbara/Kimberly and Indian Ocean. Marine sedimentary records imply KT-LE has been emitting dust throughout the Quaternary and potentially longer, although dust deposits linked directly to KT-LE exist only for the past ~55 kyr. The southern section of KT-LE emits little dust today; however, palaeo-aeolian sediments outcrop in, and mantle, the southern lake margins, pointing to the possibility of major net dust deflation episodes over the last glacial cycle. The spatial extent of net-deflation episodes remains uncertain. Only one event, at 30–15 ka, is evident in both lake sedimentary records and distal dust records. Over the late Pleistocene, it remains difficult to quantity the contribution of KT-LE sediment to Australia's dust load, although estimates suggest KT-LE generated 13% and 22% of Australia's dust load over the last 80 and 40 ka, respectively. Modern-day/Holocene dust emissions are periodic and appear coupled to arid-humid cycles, with sediment recharge a key contributing factor. During the late Pleistocene, controls on emissions are less clear, but likely coincided with large-scale changes in moisture. Despite 80 years of dust research at KT-LE, there remains much to learn about climate–landscape interactions and dust generation in Australia's arid heart.